New applications for slowing down of high-energy heavy ions - Maier, Michael; Justus Liebig University Giessen (My University, 2004)
In this thesis the charge-state distribution and energy loss of relativistic nickel and xenon ions in the energy range from 30 to 500 MeV/u were studied. The experiments were performed using the magnetic spectrometer FRS at GSI. In several experimental runs the slowing down data for nickel and xenon ions in various target materials ranging from Z = 4 to 79 was measured. The main goal of this experiment was to obtain slowing-down data above 30 MeV/u to improve predictions in this energy regime. Furthermore a technique to reduce the momentum spread of relativistic nickel and cobalt fragments, called 'range-focusing', was investigated. The range-focusing technique was examined to improve the efficiency of stopping relativistic ion beams produced in fragmentation reactions in thin layers of matter. This technique, to thermalize ions for high precision experiments is an essential part for low energy experiments of future in-flight separators. Finally the present status of the development and assembly of a setup for stopping relativistic ions using the range focusing technique, the FRS ion catcher, is described in the last part of this thesis.
New applications for slowing down of high-energy heavy ions
Neue Anwendungen der Abbremsung hochenergetischer Schwerionen
Keywords: Energieverlust; Abbremsvermögen; Ladungsverteilung; Reichweitenfokussierung; Ionen-Catcher; energy loss; stopping power; charge state distribution; range focusing; Ion-Catcher; ddc:530